Wizerunek Czechów i Polaków na łamach prasy polskiej z 1919 roku kontekście konfliktu o Śląsk Cieszyński - Urbaniak, Robert (Acta Universitatis Lodziensis. Folia Historica, 2003)
The conflict dating back to the year 1919, between the reviving Polish country and the Czech Republic, concerning a little, however rich and strategically important, territory of Śląsk Cieszyński, was not left unnoticed by the Polish press. The papers followed the constantly changing situation of the region in dispute. The press interest in the problem escalated when the Czech army invaded the area of Śląsk on 23rd January 1919. The army, according to the agreement made between the local Polish and Czech authorities, was supposed to support the Poles. The first pages of papers provided the descriptions of the battles, information about the situation of population and the reports of witnesses. This article attempts to illustrate the position of Polish press towards the actions taken by the Czech army on the occupied area. The image of the inhuman Czech enemy was contrasted with the picture of heroic defenders of the home - the Poles. Similarly, the relations of this kind can be found in most press organizations of the period in concern, regardless of the political option being represented. Press had great influence on public opinion and, after all, was regarded as a very important opinion-making agent. Consequently, the information it carried was expected to be more precise and reliable. However, the articles describing the events mentioned above raise doubts about the authors’ objectivity. Perhaps such position enabled the press to organize some charity campaigns for the inhabitants of Śląsk Cieszyński, or to motivate Polish society tired of World War I. There is no doubt that the press is an extremely rich historic source. Nevertheless, it should be emphasized that it requires to be treated with great awareness and some dose of criticism.